Gender in modern Greek historiography - Papadogiannis, Nikolaos (Historein, 2017)
This article analyses the emergence and development of the study of gender in modern Greek historiography in the broader sense, exploring works that incorporate, even to a minor extent, the gender factor. It shows that despite the manifold barriers that gender historians have faced, there has been a slow but steady process of diffusion of gender in modern Greek historiography in general. The article also shows that historical research on gender relations in Greece initially focused on the study of women, historicising, however, their relations with men. Thus, in line with what Kantsa and Papataxiarchis argue about the relevant scholarship at the international level, no linear transition from the study of women to the examination of gender relations occurred. What has transpired in the last two decades, however, is that the relevant historiography has gradually broadened to encompass a more systematic analysis of the (re)making of masculinities. It has also been enriched by the study of the intersection of gender and age as well as of transnational flows and their impact on gender, tendencies that have been slightly neglected in other reviews of the study of gender in Greek historiography.